Performance analysis of GaN based dual active bridge converter for electric vehicle charging application - Snehalika Snehalika; Ranjeeta Patel; Chinmoy Kumar Panigrahi (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The research work proposes a Gallium Nitride (GaN) based dual active bridge (DAB) converter for electric vehicle (EV) charging applications. The wide bandgap semiconductor device, GaN is implemented in the DAB topology of an Isolated Bidirectional DC-DC converter (IBDC). GaN-based DC-DC converters lead to higher efficiency, smaller size, faster charging, and reduced heat generation improving the overall performance of the EV charging system. The performance characteristics of GaN based DAB converter is analyzed both in simulation and hardware for EV charging application. The same analysis is extended to a Si based DAB converter and comparative results are presented. A 14.25 kW GaN based DAB and 10.5 kW Si based DAB is designed and evaluated using LTspice XVII software and a scaled-down prototype of 0.612 kW GaN based DAB and 0.25 kW Si based DAB is presented for experimental validation. Result analysis under similar operating conditions indicated an improvement of 36% more output power transfer on the GaN based DAB over the traditional Si based DAB. The developed prototype showcased improved levels of power, voltage, and current under same operating conditions. The power transmission in the developed DAB based IBDC topology is controlled using the single-phase-shift (SPS) control strategy.